2019
DOI: 10.1111/tbj.13400
|View full text |Cite
|
Sign up to set email alerts
|

BRCAmutation characteristics in a series of index cases of breast cancer selected independent of family history

Abstract: Certain genetic predisposition factors, such as BRCA1 and BRCA2 mutations play a pivotal role in familial breast cancer development in both males and females. Due to this, the importance and necessity of genetic screening to identify mutations affecting the population is paramount. Undergoing genetic screenings allows for a more knowledgeable risk assessment for the patients and their care providers. The aim of this study was to evaluate the prevalence of BRCA1/BRCA2 mutated genes in the Turkish population amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(26 reference statements)
2
6
0
1
Order By: Relevance
“…We think that other cancer related genes may play an important role for cancer predisposition and progression, and should be considered for further investigation. Additionally, the positivity rates were similar with our previous study of 129 patients with a different cohort of breast cancer cases due to the only shared data focusing on selected Turkish cases independent of family history [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We think that other cancer related genes may play an important role for cancer predisposition and progression, and should be considered for further investigation. Additionally, the positivity rates were similar with our previous study of 129 patients with a different cohort of breast cancer cases due to the only shared data focusing on selected Turkish cases independent of family history [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast with the literature and our previous study, we found more clinically- relevant variations in the BRCA2 gene than BRCA1 . The majority of these BRCA2 variants were classified as VUS and likely pathogenic rather than pathogenic [ 16 ]. We assume the reason is due to the lack of an in depth research on many of these Turkish-population-specific BRCA variants.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies investigating BRCA mutations in Turkey, and the BRCA carriage rates in patients with breast cancer are not known. [16][17][18] BRCA1 carriage was observed more frequently in some studies, while BRCA2 carriage in others, as in our study. On the other hand, the presented BRCA1 and BRCA2 frequencies fail to reflect the general population rates, since the study we presented was not conducted to elucidate the BRCA carrier frequency of the population.…”
Section: Discussionsupporting
confidence: 80%
“…BrCa death rates were significantly higher in developed countries compared to developing countries (15.0 vs. 12.8 per 100,000) [1,2]. Most cases of BrCa are sporadic, but an estimated 5-10% have a genetic predisposition related to, among other things, a family history of cancer in first-degree relatives or carrying genetic mutations [3,4].…”
Section: Introductionmentioning
confidence: 99%